Preparation and characterization of a novel environmentally friendly phenol–formaldehyde adhesive modified with tannin and urea. (April 2016) - Li, Cheng; Zhang, Jizhi; Yi, Zhao; Yang, Hua; Zhao, Bin; Zhang, Wei; Li, Jianzhang
Abstract: The application of phenol–formaldehyde (PF) resin adhesive has been greatly limited due to its toxicity, non-renewability and high-cost. Tannin, which is mostly extracted from renewable bark, could serve as an environmentally friendly bio-based polyphenol material. In this paper, phenol–tannin–urea–formaldehyde (PTUF) resins were prepared by copolymerization of tannin, urea, phenol and formaldehyde. Plywood bonded with those resins was prepared as well. The properties of PTUF resins were characterized by Fourier transform infrared spectroscopy (FTIR) and thermal gravimetric analysis (TGA). The results showed that the bonding strength of plywood bonded with the optimized PTUF resin could meet the Chinese National Standard (GB/T 17657-2013) for type I plywood. The optimized formula of PTUF resin adhesive was as follows: T /( P + T )=20%, U /( P + T )=30%. The bonding strength of plywood bonded with the optimized PTUF resin was 0.86 MPa, and the formaldehyde emission was 0.13 mg/L which would meet the requirement of E0 class plywood in accordance with Chinese National Standard (GB/T9846.1-9846.8-2004). TGA results showed that the thermal stability of the PTUF resin was better than that of PF resin in the initial thermal degradation. Therefore, the optimized PTUF resin is a promising substitution of PF resin in some aspects of the wood industry.